Crush Syndrome of Children in Kahramanmaraş Earthquake: A Single Center Experience in Malatya - Şenay Zırhlı Selçuk; Ahmet Taner Elmas; Yılmaz Tabel (AVES Yayincilik, 2024)
Objective: Natural disasters cause enormous environmental, economic, and human losses. Children are the most vulnerable group and face severe consequences. While the primary cause of post-traumatic death is direct injury, the secondary cause is crush syndrome (CS). In this study, we aimed to share our experience in the management of children with CS during disasters by evaluating the clinical and laboratory outcomes of a group of 26 paediatric patients. Materials and Methods: Age, weight, length of time under rubble, laboratory results, and characteristics of crush injuries were assessed in 26 paediatric patients admitted to the emergency department after the earthquake. Diagnostic criteria for CS were established and the need for dialysis, hyperbaric oxygen or amputation and its determinants were assessed. Results: Crush syndrome was observed in 10 of the 26 patients. Significant differences in creatinine, aspartate aminotransferase, alanine aminotransferase, creatine kinase, hematocrit, pH, HCO3, and myoglobin levels were observed between patients with and without CS. None of the individuals rescued from the rubble within the first 6 hours had symptoms associated with CS. These 10 patients who developed CS were rescued within the first 48 hours of the earthquake, while 2 siblings were rescued after 81 hours and did not develop CS. Conclusion: The fact that the children were rescued from the rubble after 81 hours without developing CS shows the importance of patience in rescue operations. In addition, the very cold weather conditions during this earthquake may have prevented the development of dehydration and acute kidney injury and reduced the possibility of CS.